(untitled) (Advancements in Homeopathic Research, 2022)
Nicotiana tabacum plant from Solanaceae family contains main alkaloid as nicotine, which is highly addictive and exposes people to harmful effects of tobacco dependency. Nicotine entering the human body through different routes of administration produces various immunological and physiological responses. The article highlights the linkage of these responses regarding the mechanism of action of nicotine on body and the corresponding symptoms observed during Homoeopathic proving that will help to understand the drug in a unique and better way.